2014
DOI: 10.1093/qjmed/hcu158
|View full text |Cite
|
Sign up to set email alerts
|

Are Gujarati Asian Indians ‘older’ for their ‘vascular age’ as compared to their ‘Chronological age’?

Abstract: The Gujarati Asian Indians are subjected to premature vascular ageing and henceforth routine screening for vascular age and risk factors prevalence is strongly advocated in this ethnic group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…It is the most common condition seen in primary care which leads to myocardial infarction, stroke, renal failure, and death if not detected early and treated appropriately. The western Indian population is more susceptible to CVDs, being affected at a younger age (≤40 years of age), with risk factors possibly also starting to show up at an early age period [1]. Prevalence of HTN increases with increasing age which could be used as a measure of its future CVD burden.…”
Section: Introductionmentioning
confidence: 99%
“…It is the most common condition seen in primary care which leads to myocardial infarction, stroke, renal failure, and death if not detected early and treated appropriately. The western Indian population is more susceptible to CVDs, being affected at a younger age (≤40 years of age), with risk factors possibly also starting to show up at an early age period [1]. Prevalence of HTN increases with increasing age which could be used as a measure of its future CVD burden.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 South Asian ethnicity itself is considered as one of the risk factor of CVD and the prevalence of various cardiovascular risk factors (CVRFs) predisposes this population to premature vascular ageing. 3 Atherosclerosis, formerly known as a disease of lipid storage is actually a complex cardiac condition involving active and chronic inflammatory process. Hypertension, diabetes, addiction, age, gender and hereditary factors all contribute to the progression of atherosclerosis; however inflammatory cells also play a vital role in this process.…”
Section: Introductionmentioning
confidence: 99%
“…A higher estimated vascular age than chronological age has been shown to be associated with components of metabolic syndrome and CV risk profiles in large crosssectional studies of general populations. 15,16 Higher Δage could predict the earlier occurrence of CV events in south Asians. In a randomized trial of 3153 subjects in southern Europeans, informing patients about their CVD risk expressed as the Heart Age tool resulted in a higher reduction in their CVD risk than the traditional methods of Framingham REGICOR risk score after 12 months follow up.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, we reported more extensively the analyses conducted by using the concept of Δage because we wanted to underline the risk related to modifiable factors and to have an index that identifies men in whom such CKD risk factors can be improved. A higher estimated vascular age than chronological age has been shown to be associated with components of metabolic syndrome and CV risk profiles in large cross‐sectional studies of general populations . Higher Δage could predict the earlier occurrence of CV events in south Asians.…”
Section: Discussionmentioning
confidence: 99%